DC-Lecture 3
DC-Lecture 3
DC-Lecture 3
1. Binary Logic
2. Algebras
3. Basic Definitions
4. Boolean Algebra
5. Algebraic Manipulation
6. Complement of a Function
Outline
1. Binary Logic
2. Algebras
3. Basic Definitions
4. Boolean Algebra
5. Algebraic Manipulation
6. Complement of a Function
Boolean Algebra & Logic Gates-
Binary Logic- Definition
AND OR NOT
x y z x y z x z
0 0 0 0 0 0 0 1
0 1 0 0 1 1 1 0
1 0 0 1 0 1
1 1 1 1 1 1
z=x•y=xy z=x+y z = x = x’
Boolean Algebra & Logic Gates-
Binary Logic (Cont.)- Switching Circuits
AND OR
Boolean Algebra & Logic Gates-
Binary Logic (Cont.)-
Graphic Symbols & Input-Output Signals of Logic Gates
1. Binary Logic
2. Algebras
3. Basic Definitions
4. Boolean Algebra
5. Algebraic Manipulation
6. Complement of a Function
Boolean Algebra & Logic Gates-
Algebras
What is an algebra?
– Mathematical system consisting of
• Set of elements
• Set of operators
• Axioms or postulates
Why is it important?
– Defines rules of “calculations”
Boolean Algebra & Logic Gates-
Algebras (Cont.)
1. Binary Logic
2. Algebras
3. Basic Definitions
4. Boolean Algebra
5. Algebraic Manipulation
6. Complement of a Function
Boolean Algebra & Logic Gates-
Basic Definition- Set
– For example:
• Given a set S, consider a*b = c and * is a binary operator.
– If (a, b) through * get c and a, b, c ∈ S, then * is a binary operator
of S.
1. Binary Logic
2. Algebras
3. Basic Definitions
4. Boolean Algebra
5. Algebraic Manipulation
6. Complement of a Function
Boolean Algebra & Logic Gates-
Boolean Algebra- George Boole (Father of BA)
2) 0 for OR because x + 0 = 0 + x = x.
Boolean Algebra & Logic Gates-
Boolean Algebra (Cont.)-
Axiomatic Definition of Boolean Algebra (Cont.)-
Axiom (3): Commutative Property
x + y = y + x and x • y = y • x
– From the symmetry of the tables.
0 0 0 0 0 0
0 1 1 1 0 0
1 0 1 1 0 0
1 1 1 1 1 1
Boolean Algebra & Logic Gates-
Boolean Algebra (Cont.)-
Axiomatic Definition of Boolean Algebra (Cont.)-
Axiom (4): Distributive Property
Q.E.D. An abbreviation of the Latin phrase “Quod Erat Demonstrandum". It literally translates as "which was to be
demonstrated", and is a formal way of ending a mathematical, logical or physical proof.
Boolean Algebra & Logic Gates-
Boolean Algebra (Cont.)- Boolean Theorems
Theorem-1 (Idempotent Law) - (b) x • x = x
Post. 2: (a) x + 0 = x, (b) x·1 = x
Proof that x • x = x Post. 4: (a) x(y + z) = xy + xz,
(b) x + yz = (x + y)(x + z)
x • x = xx + 0 by 2(a) Post. 5: (a) x + x’=1, (b) x·x’ = 0
= xx + xx’ by 5(b)
= x(x + x’) by 4(a)
=x•1 by 5(a)
=x by 2(b)
Q.E.D.
= (x + x’)(x + 1) by 5(a)
= x + x’ 1 by 4(b)
= x + x’ by 2(b)
=1 by 5(a)
Q.E.D.
Boolean Algebra & Logic Gates-
Boolean Algebra (Cont.)- Boolean Theorems
Theorem-2- (b) x • 0 = 0
Post. 2: (a) x + 0 = x, (b) x·1 = x
Proof that x • 0 = 0 Post. 4: (a) x(y + z) = xy + xz,
x • 0 = 0 + (x • 0) by 2(a) (b) x + yz = (x + y)(x + z)
Post. 5: (a) x + x’=1, (b) x·x’ = 0
= (x • x’) +(x • 0) by 5(b) Th2(a): (a) x + 1 =1
= x(x’ + 0) by 4(a)
= x • x’ by 2(a)
=0 by 5(b)
Q.E.D.
Boolean Algebra & Logic Gates-
Boolean Algebra (Cont.)- Boolean Theorems
Theorem-3- (Involution Law) ( x’ )’ = x
Post. 2: (a) x + 0 = x, (b) x·1 = x
Proof that (x’)’ = x Post. 4: (a) x(y + z) = xy + xz,
(b) x + yz = (x + y)(x + z)
Post. 5: (a) x + x’=1, (b) x·x’ = 0
Home Assignment
Prove That:
(1) (x + y)’ = x’y’ , (2) (xy)’ = x’ + y’
0 0 1 1 0 1 1 0 1 1
0 1 1 0 1 0 0 0 1 1
1 0 0 1 1 0 0 0 1 1
1 1 0 0 1 0 0 1 0 0
Boolean Algebra & Logic Gates-
Boolean Algebra (Cont.)- Boolean Theorems
Theorem-6- (Absorption Law) (a) x + xy = x
Post. 2: (a) x + 0 = x, (b) x·1 = x
Proof that x + x y = x Post. 3: (a) x+y=y+x, (b) x·y=y·x
Post. 4: (a) x(y + z) = xy + xz,
x + x y= x • 1 + x • y by 2(b) (b) x + yz = (x + y)(x + z)
= x(1 + y) by 4(a) Post. 5: (a) x + x’=1, (b) x·x’ = 0
Th. 2(a): (a) x+1=1
= x(y + 1) by 3(a)
=x•1 by Th 2(a)
=x by 2(b)
Q.E.D.
Boolean Algebra & Logic Gates-
Boolean Algebra (Cont.)- Boolean Theorems
Theorem-6- (Absorption Law) (b) x(x + y) = x
Post. 2: (a) x + 0 = x, (b) x·1 = x
Post. 3: (a) x+y=y+x, (b) x·y=y·x
Proof that x(x + y) = x Post. 4: (a) x(y + z) = xy + xz,
(b) x + yz = (x + y)(x + z)
Post. 5: (a) x + x’=1, (b) x·x’ = 0
By two methods: Th. 2(a): (a) x+1=1
̶ Duality, OR,
̶ Truth table
x y x+y x(x+y)
0 0 0 0
0 1 1 0
1 0 1 1
1 1 1 1
Boolean Algebra & Logic Gates-
Boolean Algebra (Cont.)- Boolean Theorems
Theorem-7- (Consensus Theorem)
Prove That:
(1) x y + x’ z + y z = x y + x’ z
(2) (x + y)•(x’ + z)•(y + z) = (x + y) • (x’ + z) (Home Assignment)
A Boolean function
– Binary variables
– Binary operators OR and AND
– Unary operator NOT
– Parentheses
Examples
– F1= x y z'
– F2 = x + y'z
– F3 = x' y' z + x' y z + x y'
– F4 = x y' + x' z
Boolean Algebra & Logic Gates-
Boolean Algebra (Cont.)- Boolean Functions (Cont.)
F2 = x + y'z
F4 = x y' + x' z
Outline
1. Binary Logic
2. Algebras
3. Basic Definitions
4. Boolean Algebra
5. Algebraic Manipulation
6. Complement of a Function
Boolean Algebra & Logic Gates-
Algebraic Manipulation-
Minimization of Boolean Expressions
1. x(x'+y) = xx' + xy = 0 + xy = xy
2. x+x'y = (x+x‘)•(x+y) = 1•(x+y) = x+y
3. (x+y)(x+y') = x+xy+xy'+yy' = x(1+y+y') = x
4. xy + x'z + yz = xy + x'z + yz(x+x')
= xy + x'z + yzx + yzx'
= xy(1+z) + x'z(1+y)
= xy +x'z
5. (x+y)(x'+z)(y+z) = (x+y)(x'+z), by duality from function 4.
(by Theorem 7: consensus theorem with duality)
Outline
1. Binary Logic
2. Algebras
3. Basic Definitions
4. Boolean Algebra
5. Algebraic Manipulation
6. Complement of a Function
Boolean Algebra & Logic Gates-
Complement of a Function
An interchange of 0's for 1's and 1's for 0's in the value of F
– E.g., By DeMorgan's theorem, Prove that: (A+B+C)' = A'B'C‘
F = (A+B+C)' = (A+X)' let B+C = X
= A'X' by theorem 5(a) (DeMorgan's Law)
= A'(B+C)‘ substitute B+C = X
= A'(B'C') by theorem 5(a) (DeMorgan's Law)
= A'B'C' by theorem 4(b) (Associative Law) x • (y • z) = (x • y) • z
F2' = [x(y'z'+yz)]'
= x' + (y'z'+yz)'
= x' + (y'z')' (yz)‘
= x' + (y+z) (y'+z')
= x' + yz‘+y‘z
Boolean Algebra & Logic Gates-
Complement of a Function (Cont.)- Example-2
A simpler procedure
– Take the dual of the function and complement each literal
1. F1 = x'yz' + x'y‘z
The dual of F1 is (x'+y+z') (x'+y'+z)
Complement each literal: (x+y'+z)(x+y+z') = F1'
2. F2 = x(y’z' + yz)
The dual of F2 is x+(y'+z') (y+z)
Complement each literal: x'+(y+z)(y’+z') = F2'